Correction: Trajectory analyses in insurance medicine studies: Examples and key methodological aspects and pitfalls. - Laura Serra; Kristin Farrants; Kristina Alexanderson; Mónica Ubalde; Tea Lallukka (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0263810.].